2015
DOI: 10.2147/ijn.s90014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cell-penetrating peptide domain from human beta-defensin 3 and characterization of its anti-inflammatory activity

Abstract: Human beta-defensins (hBDs) are crucial factors of intrinsic immunity that function in the immunologic response to a variety of invading enveloped viruses, bacteria, and fungi. hBDs can cause membrane depolarization and cell lysis due to their highly cationic nature. These molecules participate in antimicrobial defenses and the control of adaptive and innate immunity in every mammalian species and are produced by various cell types. The C-terminal 15-mer peptide within hBD3, designated as hBD3-3, was selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Further investigations are required to verify these possible mechanisms of action. Nevertheless, our results would provide a unique property of a peptide with anti-inflammatory potential, and support previous observation that the ability of peptides to block LPS-induced responses does not rely exclusively on the ability to bind to LPS [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further investigations are required to verify these possible mechanisms of action. Nevertheless, our results would provide a unique property of a peptide with anti-inflammatory potential, and support previous observation that the ability of peptides to block LPS-induced responses does not rely exclusively on the ability to bind to LPS [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…Another possibility is that the KLK peptide may penetrate macrophages and subsequently interfere with signaling molecules in the inflammatory pathway to inhibit inflammation. A range of AMPs have been recognized as cell-penetrating peptides and have also been reported to be capable of inhibiting NF-κB signaling and suppressing inflammation [ 36 , 37 ]. Further investigations are required to verify these possible mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a model of lung inflammation, hBD3-3 was shown to reduce interstitial infiltration by neutrophils. HBD3-3 was able to downregulate the nuclear factor-kappa B (NF-κB)-dependent inflammatory response via direct suppression of the phosphorylated-nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor alpha (IκBα) degradation and downregulation of the p65 unit of activated NF-κB [25]. …”
Section: Introductionmentioning
confidence: 99%
“…However, this therapeutic application of full length HBD3 is limited by its molecular size, the complexity of disulfide pairing, and attenuated activity at elevated ionic strength. To overcome these limitations and identify the active peptide fragments within HBD3, the C-terminal HBD3 peptide was modified by substituting serine for cysteine residues, and shown to have retained its anti-microbial activity [42]. Recent reports showed that HBD3-C15 peptide could attenuate LPS-induced bone resorption, by disrupting podosome belt formation in osteoclasts and suppressing their differentiation [43].…”
Section: Discussionmentioning
confidence: 99%